Respuesta :

Space

Answer:

f(-2) = -4

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Step-by-step explanation:

Step 1: Define

f(x) = 3x + 2

f(-2) is x = -2

Step 2: Evaluate

  1. Substitute in x:                    f(-2) = 3(-2) + 2
  2. Multiply:                               f(-2) = -6 + 2
  3. Add:                                     f(-2) = -4

Answer    4

Step-by-step explanation:

3(-2)= -6

-6+2= -4

ACCESS MORE